Synthesis and structural comparisons of five new fluorinated metal organic frameworks (F-MOFs) - Pachfule, Pradip; Dey, Chandan; Panda, Tamas; Banerjee, Rahul (Crystengcomm, 2010)
A series of fluorinated metal-organic frameworks (F-MOFs) have been successfully synthesized under hydrothermal condition using 4,40-(hexafluoroisopropylidene) bis(benzoic acid) (C(17)H(10)F(6)O(4), H(2)hfbba) as a flexible dicarboxylate building block, Cu(+2) and various heterocyclic co-ligands. These F-MOFs formulated as [Cu(hfbba)(phen)(2)]center dot 2(H(2)hfbba)(H(2)O)(HCO(2)) (F-MOF-1), [Cu(hfbba)(2)(2,2'-bipy) 2(H(2)O)] (F-MOF-2), [Cu(hfbba)(4,4'-dime-2,2'-bipy)(HCO(2))]center dot(hfbba)(H(2)O) (F-MOF-3), [Cu(2)(hfbba)(2)(3-mepy)(2)]center dot(DMF) 2(3-mepy) (F-MOF-4), and [Cu(hfbba)(2)(phen)(2)]center dot 0.5(DMF) (F-MOF5) (hfbba = 4,4'-(Hexafluoroisopropylidene) bis(benzoate), phen 1,1'-phenanthroline; 2,2'-bipy 2,2'-bipyridine; 4,4'dime-2,2'-bipy 4,4'-dimethyl 2,2'-bipyridine; 3-mepy 3-methyl-pyridine and DMF dimethyl formamide) display interesting H-bonded, 1D and 2D structural features. All these F-MOFs were structurally determined by single-crystal X-ray diffraction. F-MOF-1 and 5 form a distorted octahedral Cu(+2) secondary building unit (SBU). F-MOF-5 forms a one-dimensional architecture constructed from Cu(2+) ions bridged by phen anions and two types of 4 hfbba ligands while in F-MOF-1, two among the three acid co-ligands are not coordinated with Cu(2+) ions. F-MOF-2 displays dinuclear SBUs within the three-dimensional frameworks whereas F-MOF-3 displays mononuclear SBUs and forms a one-dimensional chain. F-MOF-4 display a interesting 2D framework with conventional Cu(2)(CO(2))(4) paddle wheel SBU. In the crystal structures four hfbba ligands, each coordinated to a dicopper paddlewheel unit via one of their carboxylate groups. Solid-state properties such as UV-vis and thermal stability of F-MOF-1-5 have also been studied.